Health-Related Quality of Life in Kidney Donors from the Last Five Decades: Results from the RELIVE Study - Gross, C. R. (2013)
Live donation benefits recipients, but the long-term consequences for donors remain uncertain. RELIVE surveyed kidney donors (N=2,455; 61% women; mean age 58, aged 24 – 94; mean time from donation 17 years, range 5 – 48 years) using the SF-36. The 95% CIs for white and African-American donors included or exceeded SF-36 norms. Over 80% of donors reported average or above average health for their age and sex (p<0.0001). Donors’ age-sex adjusted physical component summary [PCS] scores declined by half a point each decade after donation (p=0.0027); there was no decline in mental component summary [MCS] scores. White donors’ PCS scores were 3 points higher (p = 0.0004) than non-whites’; this difference remained constant over time. 9% of donors had impaired health (PCS or MCS score > 1 SD below norm). Obesity, history of psychiatric difficulties, and non-white race were risk factors for impaired physical health; history of psychiatric difficulties was a risk factor for impaired mental health. Education, older donation age, and a first degree relation to the recipient were protective factors. 1% reported that donation affected their health very negatively. Enhanced pre-donation evaluation and counseling may be warranted, along with ongoing monitoring for overweight donors.